Determinants of company indebtedness in the construction industry - Honková, Irena; Heckenbergerová, Jana; Kladivová, Alena (Česká zemědělská univerzita v Praze, 2021)
The aim of this paper is to reveal the determinants of indebtedness in the construc-tion industry companies. The construction industry is a specific sector where pay-ment morale is generally poor. It gradually negatively affects other companies in the following sectors. Finding the essential determinants of corporate indebtedness can prevent liquidity problems. Based on a literature review, the following determinants were selected for analyses: share of fixed assets, interest rate, return on assets, size of the company and its age. Correlation analysis and multiple linear regression analysis have been chosen to de-termine the influence of the determinants within years 2016-2019. It was found that the generally recommended fixed asset share determinant was not an appropriate determinant and its possible effect on indebtedness was also proven to be insignificant. Surprisingly interest rates have also classified as insignifi-cant. Significant determinants negatively affecting indebtedness for construction companies were determined as enterprise size and duration. The most important de-terminant was the return on assets with negative influencing outcome.
Determinanty zadluženosti ve stavebním průmyslu
Keywords: indebtedness; capital structure; return on asset; construction industry; zadluženost; kapitálová struktura; rentabilita aktiv; stavební průmysl